Exploring Fatigue Effects on Performance Variation of Intensive Brain–Computer Interface Practice - Li, Songwei; Duan, Junyi; Sun, Yu; Sheng, Xinjun; Zhu, Xiangyang; Meng, Jianjun (Frontiers in Neuroscience, 2021)
Motor Imagery (MI) is an endogenous mental process and is commonly used as an electroencephalogram (EEG) based Brain-computer interface (BCI) strategy. Previous studies of P300 and MI-based (without online feedback) BCI have shown that mental states like fatigue can negatively affect participants' EEG signatures. However, exogenous stimuli cause visual fatigue, which might have a different mechanism than endogenous tasks do. Furthermore, subjects could adjust themselves if online feedback is provided. In this sense, it's still unclear that how fatigue affects online MI-based BCI performance. With this question, twelve healthy subjects are recruited to investigate this issue, and a motor-imagery-based online BCI experiment is performed for four sessions on different days. The first session is for training, and the other three sessions differ in rest condition and duration: no rest, 16min eyes-open rest, 16min eyes-closed rest, arranged in a pseudo-random order. Multidimensional fatigue inventory (MFI) and short stress state questionnaire (SSSQ) reveal that general fatigue, mental fatigue, and distress have increased, while engagement has decreased significantly within certain sessions. However, the BCI performances, including percent valid correct (PVC) and information transfer rate (ITR), show no significant change across 400 trials. The results suggest that although the repetitive MI task has affected subjects' mental states, their BCI performances, and feature separability within a session are not affected by the task significantly. Further electrophysiological analysis reveals that alpha-band power in the sensorimotor area has an increasing tendency while ERD modulation level has a decreasing trend. During the rest time, no physiological difference has been found in the eyes-open rest condition; on the contrary, alpha-band power increase and subsequent decrease appear in eyes-closed rest condition. In summary, this experiment shows evidence that mental states can change dramatically in the intensive MI-BCI practice, but BCI performances could be maintained.